Rethinking the subject, reimagining worlds - Ruddick, Susan M (Dialogues in human geography, 2017)
The ecological crisis is also an ontological crisis. It raises questions about our ethical response-ability to this world, calling for a rethinking of the human–nature divide. Vitalist approaches and scholarship on the affective turn have shifted our understanding of our relations to nonhuman others, but they remain constrained: limited to proximate attachments; ambivalent or agnostic in the face of conflict; unable to move beyond the celebration of a lively earth. At issue I feel is a methodological individualism that haunts these offerings when confronted with questions of the ethical composition of a larger whole. Building upon Sharp’s invitation to explore ‘our continuity with nonhuman agencies’, I investigate the ethical basis for a reimagined subject in a series of becomings: the becoming nature of God, becoming animal of man, and becoming sign of earth. Drawing on the writings of Spinoza, Deleuze and Guattari, and Peirce, I rework this familiar terrain on two counts. First, I examine how the content of each becoming invokes distinct relational dynamics and complicates the ‘problem of composition’. Second, I draw on Spinoza’s differentiated concept of power (as potentia and potestas) and the concept of the composite individual to suggest an alternative way of framing our collaborations with the nonhuman world.